2014
DOI: 10.4161/cbt.28931
|View full text |Cite
|
Sign up to set email alerts
|

SAHA and S116836, a novel tyrosine kinase inhibitor, synergistically induce apoptosis in imatinib-resistant chronic myelogenous leukemia cells

Abstract: Limited treatment options are available for chronic myelogenous leukemia (CML) patients who develop imatinib mesylate (IM) resistance. Here we proposed a novel combination regimen, a co-administration of S116836, a novel small molecule multi-targeted tyrosine kinase inhibitor that was synthesized by rational design, and histone deacetylases inhibitor (HDACi) suberoylanilide hydroxamic acid (SAHA), to overcome IM resistance in CML. S116836 at low concentrations used in the present study mildly downregulates aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…For example, a phase I study of vorinostat with decitabine-treated R/R AML patients who had mixed lineage leukemia (MLL) demonstrated a 35% composite complete response (CRC) rather than a [115]. Hence, combining HDACis with other chemotherapeutic agents is considered to be an effective way to enhance tumor drug sensitivity by improving the cellular efficacy and toxicity of HDACis to tumor cells [116][117][118][119][120][121][122][123][124][125] (Table 3 and Table 4). To date, the different mechanisms of HDACis combined with chemotherapeutic agents such as topoisomerase inhibitors, platinumbased chemotherapeutics, proteasome inhibitors, tyrosine kinase pathway inhibitors and epigenetic modifiers for advanced or drug-resistant hematological malignancies include (1) acetylating histones and inducing p21-CDK-mediated cell cycle arrest; (2) inducing apoptosis by regulating the expression of pro-and antiapoptotic genes through the intrinsic or extrinsic pathway; (3) inducing DNA damage and oxidative stress; (4) activating BTK (in CLL) or inhibiting ERK (in MM) and AKT (in CML) signaling pathways; and (5) regulating the expression of drug resistance-related molecules, such as downregulating BCR-ABL and upregulating Bim in hematological malignancies and downregulating CD44 in multiple myeloma (MM), NF-κB in ALL, γ-catenin in CML, and BRCA1, CHK1 and RAD51 in AML [126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144][145].…”
Section: The Application Of Hdacis In Malignant Hematopoiesismentioning
confidence: 99%
“…For example, a phase I study of vorinostat with decitabine-treated R/R AML patients who had mixed lineage leukemia (MLL) demonstrated a 35% composite complete response (CRC) rather than a [115]. Hence, combining HDACis with other chemotherapeutic agents is considered to be an effective way to enhance tumor drug sensitivity by improving the cellular efficacy and toxicity of HDACis to tumor cells [116][117][118][119][120][121][122][123][124][125] (Table 3 and Table 4). To date, the different mechanisms of HDACis combined with chemotherapeutic agents such as topoisomerase inhibitors, platinumbased chemotherapeutics, proteasome inhibitors, tyrosine kinase pathway inhibitors and epigenetic modifiers for advanced or drug-resistant hematological malignancies include (1) acetylating histones and inducing p21-CDK-mediated cell cycle arrest; (2) inducing apoptosis by regulating the expression of pro-and antiapoptotic genes through the intrinsic or extrinsic pathway; (3) inducing DNA damage and oxidative stress; (4) activating BTK (in CLL) or inhibiting ERK (in MM) and AKT (in CML) signaling pathways; and (5) regulating the expression of drug resistance-related molecules, such as downregulating BCR-ABL and upregulating Bim in hematological malignancies and downregulating CD44 in multiple myeloma (MM), NF-κB in ALL, γ-catenin in CML, and BRCA1, CHK1 and RAD51 in AML [126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144][145].…”
Section: The Application Of Hdacis In Malignant Hematopoiesismentioning
confidence: 99%
“…The drug concentration resulting in 50% inhibition of cell growth (IC 50 ) was determined. Combination index (CI) studies with MDA‐MB‐231 cells were performed as previously described …”
Section: Methodsmentioning
confidence: 99%
“…Combination index (CI) studies with MDA-MB-231 cells were performed as previously described. 26 Colony-formation assay MDA-MB-231 and HS-578T cells (2 × 10 5 /well) plated in 6-well plates were treated with 0 or 3.75 μM DCC-2036 for 48 h; then, the cells were collected, washed with PBS and cultured in DMEM lacking drugs. Fourteen days later, the cells were washed with PBS, fixed in 10% methanol for 15 min, and stained with Giemsa for 20 min.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…5-Aza-CdR was first characterized 30 years ago and it functions as a mechanism-dependent suicide inhibitor of DNA methyltransferases, with which genes silenced by hypermethylation can be reactivated (25). SAHA is a pan-HDAC inhibitor, and the antitumor effects of SAHA have been reported in chronic myelogenous leukemia (26), lung (27), pancreatic (28), liver (29), cervical (30), head and neck (31), breast (32) and ovarian cancers (33). Our results showed that 5-Aza-CdR or SAHA could inhibit pancreatic cancer cell proliferation in a dose-and time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%